1994
DOI: 10.1089/thy.1994.4.55
|View full text |Cite
|
Sign up to set email alerts
|

Human Thyroxine Absorption: Age Effects and Methodological Analyses

Abstract: Experience with the use of simultaneous oral and iv radioiodine tracers of thyroxine (T4) to measure T4 absorption was reviewed to determine the effect of advanced age on T4 absorption and to search for acceptable simplifications in the measurement methodology. (1) Age effect: In control subjects, T4 absorption did not differ with age between 21 and 69 years; it averaged 62.8 +/- 13.5% (SD) in subjects over age 70 compared with 69.3 +/- 11.9% in subjects aged 21-69 (p < 0.001). We conclude that, because of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 16 publications
0
26
0
2
Order By: Relevance
“…It has been reported that 65–75% of oral L-T4 and 69–99% of oral L-T3 is absorbed [72,73,74,75]. Assuming 80% absorption of L-T4 and 100% absorption of L-T3 the dose of L-T4 and L-T3 in L-T4 + L-T3 combination therapy is calculated as follows (table 6, method B1):…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that 65–75% of oral L-T4 and 69–99% of oral L-T3 is absorbed [72,73,74,75]. Assuming 80% absorption of L-T4 and 100% absorption of L-T3 the dose of L-T4 and L-T3 in L-T4 + L-T3 combination therapy is calculated as follows (table 6, method B1):…”
Section: Resultsmentioning
confidence: 99%
“…B2: Daily L-T4 dose that has been absorbed and produced normal TSH is 0.8x (assuming 80% absorption of L-T4) [72,73,74,75]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are substantial interindividual variations in LT4 requirements. These requirements are dependent on patient's age, gender and body size, lean body mass, body mass index (BMI), and body surface area [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Thyroxine is a widely used drug in the treatment of patients with thyroid disease, mainly as replacement therapy for hypothyroidism 27 and efficient absorption of oral thyroxine appears to be important to ensure optimal treament. 28 We identified one recent case-control study, 20 which addressed whether euthyroid multinodular goitre patients with H. pylori-gastritis and hypochlorhydria have an increased need for thyroxine: in particular, the study was performed on 113 goitre patients with hypochlorhydria (H. pylori-related atrophic and non-atrophic gastritis) and 135 goitre patients without any gastric disorders and showed that the daily thyroxine requirement was significantly (by 22-34%) higher in the hypochlorhydric group than in controls. Furthermore, the occurrence of H. pylori infection in a subset of patients led to an increase in the daily need for thyroxine which was nearly reversed on eradication treatment associated with a 94% decrease in thyrotropin levels.…”
Section: Results Of Selected Studiesmentioning
confidence: 99%